Ruthenium-decorated vanadium pentoxide for room temperature ammonia sensing. Issue 49 (12th September 2019) - Birajdar, Shobha N.; Hebalkar, Neha Y.; Pardeshi, Satish K.; Kulkarni, Sulabha K.; Adhyapak, Parag V.
Abstract : Layer structured vanadium pentoxide (V2 O5 ) microparticles were synthesized hydrothermally and successfully decorated by a facile wet chemical route, with ∼10–20 nm sized ruthenium nanoparticles. Abstract : Layer structured vanadium pentoxide (V2 O5 ) microparticles were synthesized hydrothermally and successfully decorated by a facile wet chemical route, with ∼10–20 nm sized ruthenium nanoparticles. Both V2 O5 and ruthenium nanoparticle decorated V2 O5 (1%Ru@V2 O5 ) were investigated for their suitability as resistive gas sensors. It was found that the 1%Ru@V2 O5 sample showed very high selectivity and sensitivity towards ammonia vapors. The sensitivity measurements were carried out at 30 °C (room temperature), 50 °C and 100 °C. The best results were obtained at room temperature for 1%Ru@V2 O5 . Remarkably as short a response time as 0.52 s @ 130 ppm and as low as 9.39 s @ 10 ppm recovery time at room temperature along with high selectivity towards many gases and vapors have been noted in the 10 to 130 ppm ammonia concentration range. Short response and recovery time, high reproducibility, selectivity and room temperature operation are the main attributes of the 1%Ru@V2 O5 sensor. Higher sensitivity of 1%Ru@V2 O5 compared to V2 O5 has been explained and is due to dissociation of atmospheric water molecules on 1%Ru@V2 O5 as compared to bare V2 O5 which makes hydrogen atoms available on Brønsted sites for ammonia adsorption and sensing. The presence of ruthenium with a thin layer of oxide is clear from X-ray photoelectron spectroscopy and that of water molecules from Fourier transform infrared spectroscopy.